2021
DOI: 10.3390/plants10122552
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Chickpea Mutant Resistant to Phelipanche aegyptiaca Pers. and Orobanche crenata Forsk

Abstract: Chickpea (Cicer arietinum L.) is a major pulse crop in Israel grown on about 3000 ha spread, from the Upper Galilee in the north to the North-Negev desert in the south. In the last few years, there has been a gradual increase in broomrape infestation in chickpea fields in all regions of Israel. Resistant chickpea cultivars would be simple and effective solution to control broomrape. Thus, to develop resistant cultivars we screened an ethyl methanesulfonate (EMS) mutant population of F01 variety (Kabuli type) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Consequently, DOXC54-like 1 enzymes are presumed to have evolved from DOXC54 clade enzymes in Fabaceae plants and are likely implicated in SL diversification specific to this plant family. Several Fabaceae plants reportedly produce putative DDHs, including medicaol ( Yoneyama et al., 2008 ; Tokunaga et al., 2015 ; Galili et al, 2021 ). DOXC54-like 1 enzymes may have a role in the conversion of orobanchol to DDHs in this plant family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, DOXC54-like 1 enzymes are presumed to have evolved from DOXC54 clade enzymes in Fabaceae plants and are likely implicated in SL diversification specific to this plant family. Several Fabaceae plants reportedly produce putative DDHs, including medicaol ( Yoneyama et al., 2008 ; Tokunaga et al., 2015 ; Galili et al, 2021 ). DOXC54-like 1 enzymes may have a role in the conversion of orobanchol to DDHs in this plant family.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ZmBX6 ( Jonczyk et al., 2008 ), CrD4H ( Vazquez-Flota et al., 1997 ), AtGSLOH ( Hansen et al., 2008 ), and E8/Sl27DOX ( Akiyama et al., 2021 ), from maize, rosy periwinkle ( Catharanthus roseus ), Arabidopsis , and tomato, respectively, catalyze the hydroxylation of DIBOA glucoside, desacetoxyvindoline, 3-butenyl glucosinolate, and lycoperoside C. Additionally, SmTIIAS ( Song et al., 2021 ) from redroot sage ( Salvia miltiorrhiza ), catalyzing the dehydrogenation of dihydrofuran to furan, is also included. Fabacyl acetate has solely been identified in pea, whereas DDHs including medicaol exhibit a broader distribution within Fabaceae plants ( Yoneyama et al., 2008 ; Tokunaga et al., 2015 ; Galili et al, 2021 ). Thus, the unique diversification pathway catalyzed by PsFOS is suggested to have emerged through the evolution of DOXC31 in different lineages of DOXC55 and DOXC54, which are presumed to be involved in SL biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional control methods include seed quarantine, trapping, manual removal, induced eradication, and chemical control [2]. Current research suggests that breeding resistant species is also an effective strategy and much work has been conducted to identify resistance (R) genes; however, the function of the R genes may be overcome by new strains of parasitic plants, as most R genes mediate race-specific resistance through a gene-for-gene mechanism [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Sun (2020) found that the tomato ccd7 mutant obtained by CRISPR/cas9 gene editing had the phenotype of lateral branches increasing and plant dwarfing [44]. Galili et al (2021) also reported that CCD7M14 encodes a truncated protein that resulted in a typical SL-deficient phenotype, increased branching, and reduced plant height, and was highly resistant to both Phelipanche aegyptiaca and Orobanche crenatain in chickpea [45].…”
Section: Introductionmentioning
confidence: 99%